Wings of fire. The graphic novel. Book five, The brightest night - Deutsch, Barry; Holmes, Mike (Comic book artist); Swirsky, Rachel; Sutherland, Tui, 1978- (New York, NY : Graphix, 2021)
Presents a graphic novelization of Tui T. Sutherland's "The Brightest Night' in which Sunny, one of the dragonets of destiny, feels guilty for leaving Starflight with Morrowseer when she finds him hurt, and fights to rescue him, but is caught up in her own trouble when she does.
Based on: The brightest night / by Tui T. Sutherland.
3.2
3-6
Keywords: Dragons -- Comic books, strips, etc. -- Juvenile fiction; Prophecies -- Comic books, strips, etc. -- Juvenile fiction; Fantasy comic books, strips, etc; Dragons -- Fiction; Prophecies -- Fiction; Fantasy; Cartoons and comics; Fantasy comics; Graphic novel adaptations; Graphic novels; Comics (Graphic works)